The acquisition of dendritic cell tolerance during malaria infection results in differential T-cell activation - Perry, James A., author; Avery, Anne, advisor (Colorado State University. Libraries, 2008)
Malaria is caused by intracellular protozoan parasites belonging to the genus Plasmodia. These single cell eukaryotes have a complex life cycle requiring both mammalian (and in certain Plasmodium species, avian) and mosquito hosts. Clinical malaria in humans and other animals is the result of red blood cell (RBC) infection. Although infection direcdy destroys erythrocytes, causing anemia, a significant degree of anemia and morbidity is the result of the host immune response. Inflammatory cytokines have been implicated in the pathogenesis of severe malaria anemia (SMA) and cerebral malaria (CM), two diseases that are responsible for most malaria-related morbidity. Therefore, understanding the regulation of host immunity and inflammatory cytokine production during malaria infection will improve our understanding of malaria related illness.

Malaria is one of the greatest medical, social and economical problems facing the majority of the world's population. The consequences of malaria infection for the host immune response continue to be a profound topic of interest and research. This dissertation is focused on several aspects of the host immune response to Plasmodium yoelii, a murine malaria parasite. The studies described herein suggest that in situations where host and parasite are well adapted, as in our model using P. yoelii and B6/B10D2 mice, malaria infection guides the immune system to preferentially produce anti-inflammatory cytokines as infection progresses. When anti-inflammatory cytokines are not produced, such as in IL-10 knockout (KO) mice, severe pathology is seen.

Initial studies, as described in chapters 2 and 3 of this dissertation, demonstrated that CD4 T cell responses to an exogenous antigen (Ova) were diminished in infected mice. Subsequent work linked this immune dysfunction to a suppressive/inhibitory population of splenic macrophages. We then showed that the capacity of purified splenic dendritic cells (DCs) to stimulate IL-2 production and T cell proliferation was equivalent to that of DCs isolated from spleens of uninfected mice, and that inhibition of IL-2 production was recapitulated when splenic macrophages from infected mice were added back to cultures of purified DCs. The specific mechanism by which macrophages inhibit IL-2 production has yet to be identified but appears to be independent of IL-10, TGF-β, nitric oxide, PGE2 and tryptophan catabolism.

When looking further at T cell responses induced by DCs from naive versus infected mice, we found that while IL-2 levels are comparable, the expression and secretion of inflammatory cytokines varied dramatically. In chapter 4, we show that the cytokine profiles obtained from T cells cultured with DCs from infected mice also varied significantly with stage of infection. Specifically, T cells activated by DCs from mice 3 days post infection (p.i.) produced high levels of IFN-γ, TNF-α and little IL-10, whereas T cells stimulated by DCs from day 17 p.i. mice predominantly produced IL-10 with little accompanying IFN-γ and TNF-α.

We then determined how the phenotype of DCs shapes T cell responses as a function of time post infection. An extensive series of cell sorting experiments indicated that DCs isolated from mice during the acute phase of infection (day 3 p.i.) produced much larger quantities of IL-12p40 and TNF-oc in response to innate immune stimuli such as LPS and CpG DNA. As the infection progressed to day 17 p.i. however, purified DCs produced statistically smaller amounts of IL-12p40 and TNF-oc while secreting larger amounts of IL- 10 as measured both by in vitro stimulation assays as well as ex vivo mRNA analysis. These data are consistent with the previously described T cell stimulation assays where DCs isolated early during infection activate IFN-γ producing T cells whereas DCs isolated late during infection induce IL-10 producing T cells. Thus malaria infection results in downregulation of pro-inflammatory cytokines and up-regulation of anti-inflammatory cytokines.

In chapter 5 we attempted to determine the mechanism of regulation. We found that IL-10 is necessary for IL-12 downregulation, but not TNF-α. Failure to down-regulate IL-12 in IL-10 KO mice was especially evident in vivo following administration of LPS to naive and infected mice. Again, lack of IL-10 had little effect on the down regulation of TNF-α with in vivo LPS stimulation. The disparate regulation of IL-12 and TNF-α is currently being explored and appears independent of NF-kB p50 as well as the MAP kinases p38 and ERK 1/2.

These changes in cytokine production a malaria infection progresses correlates to clinical severity of disease. Downregulation of IL-12 (and IFN-γ indirectly) by IL-10 protects the host from inflammation-induced pathology. Mice lacking IL-10 develop significantly more hepatic necrosis and greater anemia despite a lower parasite burden compared with wild type mice. Our findings are consistent with epidemiological data from human malaria infections where increased pro- to anti-inflammatory cytokine ratios are correlated with an increased severity of malaria syndromes such as severe malarial anemia, cerebral malaria and placental malaria.

The observation that DCs play a dominant role in guiding the activation of IL-10 producing anti-inflammatory T cells and that IL-10 is responsible for mitigating pathology during murine malaria infection provides a basis for the development of potential therapeutics utilizing this phenomenon. One hypothetical use for such information would be the production of an "anti-disease" vaccine where IL-10 producing DCs would be used to specifically activate an anti-inflammatory adaptive immune response. Clearly, more research will be necessary before such trials become feasible as there is a tight balance between too much inflammation and too little inflammation in the context of malaria infection both in humans and animals, alike.
Keywords: anemia; dendritic cells; IL-10; IL-12; malaria; cellular biology; pathology; epidemiology; immunology